The Effect of ‘Free4Talk’ Online Language Platform Usage on Enhancing University Students’ Speaking English Skills - Bahar, Tanzila; Dalimunte, Muhammad (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study investigated the impact of the Free4Talk online language platform on enhancing university students' English speaking skills. Using a quantitative descriptive approach with a total sampling method of 50 participants, the research employed a speaking test to evaluate university students' English speaking skills. Data analysis using Partial Least Square (PLS) methodology revealed a significant positive effect of Free4Talk usage on students' speaking skills (t-statistic = 17.140, p < 0.05). The platform demonstrated substantial influence across all speaking components, with particularly strong effects on fluency (loading factor = 0.907) and grammar (loading factor = 0.903). The R² value of 0.637 indicates that 63.7% of the variation in students' speaking skills can be attributed to Free4Talk usage. The findings denoted that Free4Talk serves as an effective tool for enhancing university students' English speaking capabilities by providing authentic interaction opportunities and immediate feedback mechanisms. The descriptive analysis further illustrates patterns of language development across different speaking components, offering insights into how virtual language exchange platforms can be optimally integrated into EFL education.